Amygdala tau pathology in preclinical autosomal dominant Alzheimer's disease. (December 2021) - Sanchez, Justin S.; Martinez, Jairo E.; Rubinstein, Zoe B.; Baena, Ana Y.; Vila‐Castelar, Clara; Fox‐Fuller, Joshua T.; Gatchel, Jennifer R.; Ramirez‐Gomez, Liliana A.; Aduen, Paula; Guzman‐Velez, Edmarie; Pluim, Celina F.; Jacobs, Heidi I.L.; et al.
Abstract: Background: The amygdala has been found to be pathologically affected in early stages of Alzheimer's disease (AD), with particular amygdala subnuclei being especially vulnerable. We used in vivo positron emission tomography (PET) imaging to examine whether amygdala tau accumulation could be observed in cognitively unimpaired PSEN‐1 mutation carriers who carry an autosomal‐dominant mutation in the Presenilin‐1 ( PSEN‐1 ) gene and are determined to develop dementia in their early 50s. We further aimed to investigate associations between amygdala tau, age, amyloid deposition, and cognition in mutation carriers and non‐carrier family members. Method: A total of 29 PSEN‐1 mutation carriers ( M age = 37.4 +/‐ 5.8 years) and 35 age‐matched non‐carriers (M age = 35.9 +/‐ 5.8 years) were recruited from the Colombia‐Boston (COLBOS) Longitudinal Biomarker Study, which follows Colombian families with autosomal‐dominant AD. Participants underwent PET, using Pittsburgh Compound B to measure mean cortical amyloid‐β and Flortaucipir for regional tau, and episodic memory testing (CERAD Word List Learning). Amygdala subnuclei were automatically segmented with FreeSurfer7. Spearman correlations were used to examine associations among amygdala tau, age, mean amyloid‐β, and memory performance. Result: Compared to non‐carriers, cognitively unimpaired mutation carriers had greater tau accumulation in the amygdala (p<0.001). Unimpaired carriers had greater tau burden in amygdala compared to neocortical regions (vs. inferior temporal: t=2.3, p=0.03), suggesting early involvement of amygdala tau. Among amygdala subnuclei, basal and accessory basal nuclei had greater tau burden compared to the other subregions (vs. lateral nucleus: t=5.5, p<0.0001) in unimpaired carriers. Greater amygdala tau burden was associated with older age (r=0.649, p<0.0001), greater mean cortical amyloid (r=0.597, p=0.001) and worse memory performance (r=‐0.433, p= 0.019) in carriers. No significant associations were observed in the non‐carrier group. Conclusion: Amygdala tau burden is associated with greater age, cortical amyloid burden, and worse memory in preclinical autosomal dominant Alzheimer's disease. These results suggest that amygdala tau accumulation is evident in preclinical Alzheimer's disease. Future studies should determine if amygdala tau (including subnuclei) can be used as an early indicator of Alzheimer's disease progression. Longitudinal studies are needed to examine the associations between amygdala tau and onset of neuropsychiatric and behavioral symptoms.